1987
DOI: 10.1093/geronj/42.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Social Desirability in Measures of Subjective Well-being: a Systematic Evaluation

Abstract: The present investigation addressed the problem of a social desirability response bias in measures of psychological well-being. Data on 150 people, between the ages of 50 and 82, yielded high correlations between three measures of well-being (the MUNSH, the LSI-Z, and the PGC) and the Edwards Social Desirability Scale, but only moderate ones between well-being scales and the Marlowe-Crowne Social Desirability Scale. Part correlations between well-being measures and an external criterion of happiness, controlli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 0 publications
4
46
0
Order By: Relevance
“…Further analyses, however, revealed that social desirability does not necessarily distort, but rather amplifies, the meaning of psychological constructs (Furnham, 1986;McCrae & Costa, 1983). Thus, controlling for social desirability does not enhance the validity of SWB measures and may even attenuate it (Diener, Sandvik, Pavot, & Gallagher, 1991;Kozma & Stones, 1987). In line with the view that contextual artifacts for attitudes may actually be inherent in attitude formation (Tourangeau & Rasinski, 1988), it is concluded, then, that self-report measures of SWB constitute a vehicle of social declarations that are part and parcel of SWB at large.…”
Section: Adaptational Implications Of the Declarative Functionsmentioning
confidence: 86%
“…Further analyses, however, revealed that social desirability does not necessarily distort, but rather amplifies, the meaning of psychological constructs (Furnham, 1986;McCrae & Costa, 1983). Thus, controlling for social desirability does not enhance the validity of SWB measures and may even attenuate it (Diener, Sandvik, Pavot, & Gallagher, 1991;Kozma & Stones, 1987). In line with the view that contextual artifacts for attitudes may actually be inherent in attitude formation (Tourangeau & Rasinski, 1988), it is concluded, then, that self-report measures of SWB constitute a vehicle of social declarations that are part and parcel of SWB at large.…”
Section: Adaptational Implications Of the Declarative Functionsmentioning
confidence: 86%
“…The role of IM scales as suppressors or moderators of the correlation between self and informant reports have been put to test several times over the years by using different scales and types of self-informant relationships. All these tests have failed to find statistical effects that would support the interpretation of IM scales as reliable validity scales (Borkenau & Ostendorf, 1992;Borkenau & Zaltauskas, 2009;Diener, Sandvik, Pavot, & Gallagher, 1991;Hunsley, Vito, Pinsent, James, & Lefebvre, 1996;Kozma & Stones, 1987;Pauls & Stemmler, 2003;Piedmont, McCrae, Riemann, & Angleitner, 2000).…”
Section: Scope Of the Present Reviewmentioning
confidence: 99%
“…A second-order factor representing general well-being has also been obtained [60]. Correlations with the LSIA range from 0.55 to 0.75 [59,64] and 0.6 with the negative score on the Bradburn scale [33].…”
Section: Single-item Health Indicators (Various Authors Circa 1965 Omentioning
confidence: 99%